The Down Syndrome in the face of Coronavirus infection (Research, Society and Development, 2021)
This study aimed to elucidate how the genetic alterations caused by Down Syndrome (DS) impact cases of involvement by SARS-CoV-2, in addition to showing how social isolation can negatively affect the lives of individuals with DS. The study adopted the qualitative literary review model, through the Google Academic, SciELO and PubMed databases, using the descriptors “Down Syndrome” and “Coronavirus”, with twenty articles being selected. It was noticed that DS is the most common genetic form of intellectual disability and the changes that trisomy 21 cause significantly impact the disease course of people with DS infected with Coronavirus, since their immune system is overactivated, with ability to generate a shower of cytokines, which will facilitate the entry of the virus into cells, thus favoring viral replication. Furthermore, it was noted that, even though social isolation is effective in combating the pandemic, it can cause several damages to the health of the population with DS, which can aggravate certain pre-existing comorbidities in this group. Therefore, the surveillance and training of this population and their families is very important, so that they can correctly prevent themselves – with an effective hand washing technique and use of barrier equipment – ​​minimizing exposure to the virus; and socialization and physical activity – even during quarantine periods and remotely – in order to preserve the emotional and physical health of these individuals